2016
DOI: 10.1007/s13187-016-1004-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Skin Cancer Preventive Behaviors Among Rural Farmers in Iran: an Application of Protection Motivation Theory

Abstract: Skin cancer is one of the most prevalent cancers, worldwide, which happens more among those with more sunlight exposure like farmers. The aim of this study was to explore the determinants of skin cancer preventive behaviors (SCPBs) among rural farmers using Protection Motivation Theory (PMT). In this cross-sectional study, multistage random sampling was employed to enroll 238 farmers referring to rural health houses (HH) in Chaldoran County, Iran. A valid and reliable instrument based on PMT variables was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
67
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 35 publications
19
67
3
Order By: Relevance
“…Pearson's correlation coefficient was used to assess convergent validity. The Cronbach's alpha coefficient of 0.7 or above was thought to be satisfactory (11). The level of significance was considered 0.05, a priori.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson's correlation coefficient was used to assess convergent validity. The Cronbach's alpha coefficient of 0.7 or above was thought to be satisfactory (11). The level of significance was considered 0.05, a priori.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, health behavior change frameworks have been widely used to address different health issues (11)(12)(13)(14). However, limited studies have applied the planning frameworks to evaluate health care interventions on infectious diseases (15) such as brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…Providing health education to exposed or susceptible individuals, the human factor of prevention, control, treatment, and dealing with health issues is pivotal to the control and prevention of the disease . Since the theory‐based interventions supply a feasible framework to improve interventions and a guide for evaluating them and they have more useful effects on health‐related behaviors, they are more beneficial than the nontheoretical methods . Results of the studies have shown that theory‐based interventions may motivate people to change their attitudes and behaviors in exposure to the sunlight .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Studies using behavioral theories such as Protection Motivation Theory (PMT) have identified unacceptable levels of threat appraisal for skin cancer among Iranian farm workers, including a study by Tazval et al, 16 which identified that approximately 60% of farm workers surveyed had very low perceived threat levels. Another study conducted among Iranian farm workers in a rural community found that perceived susceptibility, rewards, and self-efficacy were the strongest and most positive, predictors of skincare protective behaviors.…”
Section: Dear Editormentioning
confidence: 99%
“…Another study conducted among Iranian farm workers in a rural community found that perceived susceptibility, rewards, and self-efficacy were the strongest and most positive, predictors of skincare protective behaviors. 17 Findings from research utilizing theories suggest that health care providers and health promotion practitioners should focus on developing theoretically-based health education programs targeting skin cancer prevention for this population using health education theories such as PMT. 16,17 Previous studies have successfully implemented PMT-based interventions to address sun protective behaviors among other Iranian populations; thus, suggesting the efficacy of using PMT or other value expectancy theories to develop a theory-based health education intervention for farmworkers.…”
Section: Dear Editormentioning
confidence: 99%